A guide to modelling priorities for managing land‐based impacts on coastal ecosystems. Issue 5 (1st February 2019) - Brown, Christopher J.; Jupiter, Stacy D.; Albert, Simon; Anthony, Kenneth R. N.; Hamilton, Richard J.; Fredston‐Hermann, Alexa; Halpern, Benjamin S.; Lin, Hsien‐Yung; Maina, Joseph; Mangubhai, Sangeeta; Mumby, Peter J.; Possingham, Hugh P.; et al.
Abstract: Pollution from land‐based run‐off threatens coastal ecosystems and the services they provide, detrimentally affecting the livelihoods of millions people on the world's coasts. Planning for linkages among terrestrial, freshwater and marine ecosystems can help managers mitigate the impacts of land‐use change on water quality and coastal ecosystem services. We examine the approaches used for land‐sea planning, with particular focus on the models currently used to estimate the impacts of land‐use change on water quality and fisheries. Our findings could also be applied to other ecosystem services. This Review encompasses modelling of: large scale drivers of land‐use change; local activities that cause such change; run‐off, dispersal and transformation of pollutants in the coastal ocean; ecological responses to pollutants; socio‐economic responses to ecological change; and finally, the design of a planning response. We find that there is a disconnect between the dynamical models that can be used to link land to sea processes and the simple tools that are typically used to inform planning. This disconnect may weaken the robustness of plans to manage dynamic processes. Land‐sea planning is highly interdisciplinary, making the development of effective plans a challenge for small teams of managers and decision makers. Synthesis and applications . We propose some guiding principles for where and how dynamic land‐sea connections can most effectively be built into planning tools. Tools that can capture pertinent processes are needed, but they must be simple enough to be implemented in regions with limited resources for collecting data, developing models and developing integrated land‐sea plans. Abstract : We propose some guiding principles for where and how dynamic land‐sea connections can most effectively be built into planning tools. Tools that can capture pertinent processes are needed, but they must be simple enough to be implemented in regions with limited resources for collecting data, developing models and developing integrated land‐sea plans.